Funky Series 2

Calculus Level 4

Evaluate the infinite series

S = k = 0 ( 1 ) k ( log 2017 2018 ) k k ! ( log 2017 2016 ) k S= \sum_{k=0}^{\infty} \frac{(-1)^k~(\log_{2017} 2018)^k}{k!~(\log_{2017} 2016)^k}

If ln ( S ) = log a ( b ) \ln(S) = -\log_a(b) , where a a and b b are integers, find the smallest possible average of a a and b b .


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ralph James
Jan 10, 2017

S = k = 0 ( 1 ) k ( log 2017 2018 ) k k ! ( log 2017 2016 ) k S=\displaystyle\sum_{k=0}^{\infty} \frac{(-1)^k~(\log_{2017} 2018)^k}{k!~(\log_{2017} 2016)^k}

= k = 0 ( 1 log 2017 2018 log 2017 2016 ) k 1 k ! \quad =\displaystyle\sum_{k=0}^{\infty}\left(\frac{-1\cdot\log_{2017} 2018}{\log_{2017} 2016}\right)^k\cdot\frac{1}{k!}

= k = 0 ( log 2017 ( 1 2018 ) log 2017 2016 ) k \quad =\displaystyle\sum_{k=0}^{\infty}\color{#D61F06}{\left(\frac{\log_{2017}(\frac{1}{2018})}{\log_{2017} 2016}\right)}^k 1 k ! \cdot\dfrac{1}{k!}

Using the reverse change-of-base formula, we can rewrite what's inside the parentheses:

= k = 0 ( log 2016 ( 1 2018 ) ) k \quad =\displaystyle\sum_{k=0}^{\infty} \color{#D61F06}{\left(\log_{2016} \left(\frac{1}{2018}\right)\right)^k} 1 k ! \cdot\dfrac{1}{k!}

If we plug in x = log 2016 ( 1 2018 ) x=\log_{2016}(\frac{1}{2018}) into the series, we have the series of the form k = 0 x k k ! = e x \displaystyle\sum_{k=0}^{\infty} \frac{x^k}{k!} = e^x for all real x x .

Therefore, S = e x = e log 2016 ( 1 2018 ) ln S = log 2016 ( 1 2018 ) = log 2016 ( 2018 ) S=e^x=e^{\log_{2016}(\frac{1}{2018})} \implies \ln S =\log_{2016}(\frac{1}{2018})=-\log_{2016}(2018) .

Thus, a = 2016 , b = 2018 a + b 2 = 2017 a=2016, b = 2018 \implies \frac{a+b}{2} = \boxed{2017} .

When you say "smallest possible average", keep in mind there are different averages ( R . M . S A . M G . M H . M ) ( R.M.S\ge A.M\ge G.M\ge H.M) . Hence be more specific.

Sarthak Sahoo - 1 year ago
Chew-Seong Cheong
Jan 14, 2017

S = k = 0 ( 1 ) k ( log 2017 2018 ) k k ! ( log 2017 2016 ) k Let x = log 2017 2018 log 2017 2016 = k = 0 ( 1 ) k x k k ! = e x = exp ( log 2017 2018 log 2017 2016 ) = exp ( ln 2018 ln 2017 ln 2016 ln 2017 ) = exp ( ln 2018 ln 2016 ) \begin{aligned} S & = \sum_{k=0}^\infty \frac {(-1)^k (\log_{2017} 2018)^k}{k! (\log_{2017} 2016)^k} & \small \color{#3D99F6} \text{Let }x = \frac {\log_{2017} 2018}{\log_{2017} 2016} \\ & = \sum_{k=0}^\infty \frac {(-1)^k x^k}{k!} \\ & = e^{-x} \\ & = \exp \left(- \frac {\log_{2017} 2018}{\log_{2017} 2016} \right) \\ & = \exp \left(- \frac {\frac {\ln 2018}{\ln 2017}}{\frac {\ln 2016}{\ln 2017}} \right) \\ & = \exp \left(- \frac {\ln 2018}{\ln 2016} \right) \end{aligned}

ln S = ln 2018 ln 2016 = log 2016 2018 \begin{aligned} \implies \ln S & = - \frac {\ln 2018}{\ln 2016} = - \log_{2016} 2018 \end{aligned}

Therefore, the average of a a and b b is a + b 2 = 2016 + 2018 2 = 2017 \dfrac {a+b}2 = \dfrac {2016+2018}2 = \boxed{2017}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...